Fluid–structure interactions of single and dual wall-mounted 2D flexible filaments in a laminar boundary layer. (January 2020) - Zhang, Xiang; He, Guowei; Zhang, Xing
Abstract: We numerically investigated the interactions of a laminar boundary layer flow with both single and dual wall-mounted 2D flexible filaments. The influences of various parameters, including bending rigidity, mass ratio, Reynolds number and interspace between two filaments, on the dynamics of the systems were explored systematically. Different modes of dynamic behavior in the single-filament and dual-filament systems were identified. The wake structures associated with different modes of dynamic behavior were compared. The physical mechanisms underlying the frequency lock-in phenomena observed in the flow-induced oscillations were also elucidated.